Virtual communities and the challenge of connecting with audiences - Monserrat, Leslie Diaz; Portal, Liena María Nieves (Advanced Notes in Information Science, 2024)
The first communication studies were born flawed by the obsession to control the behavior of audiences. However, as the North American school of communication consolidated, they understood that there were social components that influenced the response of broadcasters and that the media could exert an overall influence with the rest of the social institutions. The media of the 20th century, designed for mass communication, could not fulfill the dreams of a hypodermic theory that ensured that every member of the audience was “attacked” by the media message. Digital social networks have come to revolutionize every aspect of modern society. Now, the messages arrive in a personalized way to each subject of communication, and artificial intelligence dominates the production of content. This paper proposes a review from the classical theory of networks to the particularities of digital social networks. In addition, it approaches the virtual community as a way to create niches of resistance in the cultural struggle, through the segmentation of audiences that allows to achieve a connection between audiences and the posts published by the media, in this specific case, the newspaper Vanguardia.